Resin composition and molded article
By combining semi-aromatic polyamide with specific amorphous resins and carbon black, the resin composition addresses the limitations of high molding shrinkage and water absorption, achieving excellent mechanical and weather resistance for precise applications.
Patent Information
- Application Number
- JP2021107867
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-29
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-06-29
AI Technical Summary
Semi-aromatic polyamide resin compositions face limitations in applications requiring precise dimensional accuracy due to high molding shrinkage and water absorption, which affect mechanical and weather resistance.
A resin composition is developed by combining semi-aromatic polyamide with specific ranges of amorphous resins and blending carbon black within a specific range, optimizing the balance of mechanical properties and weather resistance.
The resulting resin composition achieves an excellent balance of mechanical properties and weather resistance, making it suitable for applications with high dimensional accuracy requirements, such as in-vehicle cameras.
Smart Images

Figure 0007655800000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition and a molded article. [Background technology]
[0002] Semi-aromatic polyamide resin compositions are expected to have excellent properties such as mechanical strength, heat resistance, and chemical resistance, and various developments have been carried out.
[0003] However, semi-aromatic polyamide resin compositions have a large molding shrinkage rate due to their crystalline nature, and also have a large dimensional change due to water absorption, so that their use in applications requiring precise dimensional accuracy has been limited.
[0004] In view of this, polyamide alloys have been proposed that reduce the mold shrinkage rate and dimensional changes due to water absorption by blending polyphenylene ether, which is an amorphous resin with low water absorption, with semi-aromatic polyamide (Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-182550 A [Patent Document 2] JP 2007-217620 A [Patent Document 3] JP 2011-46781 A [Patent Document 4] Special Publication No. 2016-509121 Summary of the Invention [Problem to be solved by the invention]
[0006] However, in recent years, for products that require high dimensional accuracy, such as vehicle-mounted cameras, the installation environments have become increasingly diverse in order to increase the amount of information they can acquire, so there is a demand for them to have both mechanical properties and weather resistance properties.
[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a resin composition having an excellent balance of mechanical properties and also excellent weather resistance, and a molded article containing the resin composition. [Means for solving the problem]
[0008] Means for Solving the Problems The present inventors conducted extensive research to solve the above problems and discovered that by combining a semi-aromatic polyamide with a specific range of amorphous resin and further blending carbon black in a specific range, a resin composition having excellent balance of mechanical properties and weather resistance can be obtained, thus completing the present invention.
[0009] That is, the present invention is as follows. [1] (A) Polyamide (B) Polyphenylene ether (C) Styrene-based resin (D) Compatibilizer (E) Inorganic filler (F) Carbon black A resin composition comprising: the component (A) is a polyamide having dicarboxylic acid units (a) containing 60 to 100 mol % of terephthalic acid units and diamine units (b) containing 60 to 100 mol % of aliphatic diamine units having 9 to 12 carbon atoms; the mass ratio (C) / (B) of the component (B) to the component (C) is 1 to 3; A resin composition, characterized in that the primary particle diameter of the component (F) is 20 nm or less, and the content of the component (F) is 2 to 7 parts by mass per 100 parts by mass of the total of the components (A), (B), and (C). [2] The resin composition according to [1], wherein the component (A) is 60 to 90 parts by mass per 100 parts by mass of the total of the components (A), (B) and (C). [3] The resin composition according to [1] or [2], wherein the component (A) has dicarboxylic acid units (a) containing 60 to 100 mol % of terephthalic acid units and diamine units (b) containing 60 to 100 mol % of 1,9-nonanediamine units and / or 2-methyl-1,8-octanediamine units. [4] The resin composition according to any one of [1] to [3], wherein the component (E) contains a fibrous inorganic filler or a needle-like inorganic filler. [5] The resin composition according to [4], wherein the fibrous inorganic filler is glass fiber. [6] The resin composition according to any one of [1] to [3], wherein the component (E) contains a plate-like inorganic filler. [7] The resin composition according to [6], wherein the plate-like inorganic filler is glass flakes. [8] A molded article comprising the resin composition according to any one of [1] to [7]. Effect of the Invention
[0010] According to the present invention, it is possible to obtain a resin composition having an excellent balance of mechanical properties and weather resistance, and a molded article containing said resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described in detail. The present embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content.
[0012] [Resin composition] The resin composition according to the present embodiment is a resin composition comprising (A) a polyamide (hereinafter also referred to as component (A)) having dicarboxylic acid units (a) containing 60 to 100 mol % of terephthalic acid units and diamine units (b) containing 60 to 100 mol % of aliphatic diamine units having 9 to 12 carbon atoms, (B) a polyphenylene ether (hereinafter also referred to as component (B)), (C) a styrene-based resin (hereinafter also referred to as component (C)), (D) a compatibilizer (hereinafter also referred to as component (D)), (E) an inorganic filler (hereinafter also referred to as component (E)), and (F) carbon black (hereinafter also referred to as component (F)), in which the mass ratio (C) / (B) of components (B) to (C) is 1 to 3, the primary particle diameter of component (F) is 20 nm or less, and the content of component (F) is 2 to 7 parts by mass relative to 100 parts by mass of the total of components (A), (B), and (C).
[0013] [(A) Polyamide] The polyamide (A) according to this embodiment has dicarboxylic acid units (a) containing 60 to 100 mol % of terephthalic acid units, and diamine units (b) containing 60 to 100 mol % of aliphatic diamine units having 9 to 12 carbon atoms.
[0014] [[Dicarboxylic acid unit (a)]] In the present embodiment, the dicarboxylic acid unit (a) contains 60 to 100 mol %, preferably 70 to 100 mol %, more preferably 80 to 100 mol %, and even more preferably 90 to 100 mol %, or may contain 100 mol % of terephthalic acid units in the unit (a). When the molar ratio is within this range, a resin composition having excellent heat resistance is obtained.
[0015] The dicarboxylic acid unit (a) may contain a dicarboxylic acid unit other than a terephthalic acid unit. Examples of such dicarboxylic acid units include, but are not limited to, units derived from aliphatic dicarboxylic acids such as malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, 2,2-dimethylglutaric acid, 3,3-diethylsuccinic acid, azelaic acid, sebacic acid, and suberic acid; alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as isophthalic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,4-phenylenedioxydiacetic acid, 1,3-phenylenedioxydiacetic acid, diphenic acid, 4,4'-oxydibenzoic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, and 4,4'-biphenyldicarboxylic acid. These units may be used alone or in combination of two or more kinds. The dicarboxylic acid units other than the above-mentioned terephthalic acid units may be contained in the dicarboxylic acid units (a) in an amount of 40 mol % or less, more preferably 30 mol % or less, even more preferably 20 mol % or less, still more preferably 10 mol % or less, and may be 0 mol %.
[0016] [[Diamine unit (b)]] The diamine unit (b) in this embodiment contains 60 to 100 mol %, preferably 70 to 100 mol %, more preferably 80 to 100 mol %, and even more preferably 90 to 100 mol %, or may contain 100 mol %, of aliphatic diamine units having a carbon number of 9 to 12. When the carbon number and the molar ratio of the diamine units are within the above ranges, a resin composition having an excellent balance between low water absorption and heat resistance is obtained.
[0017] From the viewpoint of achieving even greater mechanical strength at high temperatures, the diamine unit (b) is preferably an aliphatic diamine unit having 9 to 10 carbon atoms, and more preferably an aliphatic diamine unit having 9 carbon atoms. The diamine units (b) may be linear or branched.
[0018] Examples of linear aliphatic diamines constituting the diamine unit (b) include, but are not limited to, 1,9-nonanediamine (also called nonamethylenediamine), decamethylenediamine, undecamethylenediamine, and dodecamethylenediamine.
[0019] Examples of aliphatic diamines constituting the aliphatic diamine unit having a substituent branched from the main chain, which constitutes the diamine unit (b), include, but are not limited to, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 2-methyl-1,8-octanediamine (also referred to as 2-methyloctamethylenediamine), and 2,4-dimethyloctamethylenediamine.
[0020] The diamine unit (b) preferably contains 1,9-nonanediamine units and / or 2-methyl-1,8-octanediamine units from the viewpoint of balance between mechanical strength, low water absorption, and heat resistance. Among them, it is preferable to use 1,9-nonanediamine units and 2-methyl-1,8-octanediamine units in combination.
[0021] When the diamine unit (b) contains 1,9-nonanediamine units and / or 2-methyl-1,8-octanediamine units, the molar ratio of 1,9-nonanediamine units to 2-methyl-1,8-octanediamine units (1,9-nonanediamine units / 2-methyl-1,8-octanediamine units) is preferably in the range of 100 / 0 to 20 / 80. The molar ratio is more preferably 95 / 5 to 60 / 40, and even more preferably 90 / 10 to 75 / 25. When the molar ratio is in this range, the resin composition tends to be particularly excellent in heat resistance.
[0022] The diamine unit (b) may contain a diamine unit other than an aliphatic diamine unit having a carbon number of 9 to 12. Examples of such diamine units include, but are not limited to, units derived from aliphatic diamines such as ethylenediamine, propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, and 2-methylpentamethylenediamine (also referred to as 2-methyl-1,5-diaminopentane); alicyclic diamines such as 1,4-cyclohexanediamine, 1,3-cyclohexanediamine, and 1,3-cyclopentanediamine; and aromatic diamines such as metaxylylenediamine. These units may be used alone or in combination of two or more kinds. The diamine units other than the above-mentioned aliphatic diamine units having 9 to 12 carbon atoms may be contained in the diamine units (b) in an amount of 40 mol % or less, more preferably 30 mol % or less, even more preferably 20 mol % or less, still more preferably 10 mol % or less, and may be 0 mol %.
[0023] Preferred examples of the polyamide (A) in this embodiment include polyamide 9,T, polyamide 10,T, and the like.
[0024] Furthermore, the polyamide (A) of this embodiment may contain lactam units such as butyrolactam, pivalolactam, ε-caprolactam, caprylolactam, enantholactam, and undecanolactam, aminocarboxylic acid units such as 6-aminocaproic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid, trivalent or higher polyvalent amine units such as bishexamethylenetriamine, and trivalent or higher polyvalent carboxylic acid units such as trimellitic acid, trimesic acid, and pyromellitic acid, within the scope of the object of this embodiment. These units may be used alone or in combination of two or more kinds. The total proportion (mol %) of these units in the polyamide (A) is preferably 20 mol % or less, more preferably 10 mol % or less, and even more preferably 5 mol % or less, based on the entire polyamide (A), and may be 0 mol %.
[0025] [(A) Polyamide content] In the resin composition of the present embodiment, when the total of components (A), (B), and (C) is 100 parts by mass, the content of component (A) is preferably 60 to 90 parts by mass, more preferably 70 to 90 parts by mass, and even more preferably 70 to 80 parts by mass. When the content of component (A) is within this range, a resin composition excellent in mechanical strength and weather resistance can be obtained.
[0026] [(B) Polyphenylene ether] The polyphenylene ether (B) in this embodiment is not limited to the following, but examples thereof include poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), etc. Furthermore, polyphenylene ether copolymers such as copolymers of 2,6-dimethylphenol and other phenols (for example, copolymers of 2,6-dimethylphenol and 2,3,6-trimethylphenol and copolymers of 2,6-dimethylphenol and 2-methyl-6-butylphenol described in JP-B-52-017880) are also included. Among these, poly(2,6-dimethyl-1,4-phenylene ether), copolymers of 2,6-dimethylphenol and 2,3,6-trimethylphenol, and mixtures thereof are preferred from the viewpoint of mechanical strength. These may be used alone or in combination of two or more.
[0027] The lower limit of the reduced viscosity of the polyphenylene ether (0.5 g / dL chloroform solution, 30° C., measured with an Ubbelohde viscometer) is preferably 0.30 dL / g or more, more preferably 0.35 dL / g or more, and even more preferably 0.38 dL / g or more. The upper limit of the reduced viscosity of the polyphenylene ether is preferably 0.80 dL / g or less, more preferably 0.75 dL / g or less, and even more preferably 0.55 dL / g or less. The combination of the lower limit and upper limit of the reduced viscosity of the polyphenylene ether is preferably 0.30 to 0.80 dL / g, more preferably 0.35 to 0.75 dL / g, and even more preferably 0.38 to 0.55 dL / g. When the reduced viscosity of the polyphenylene ether (B) is in the above range, the impact resistance and heat resistance are further improved. (B) The polyphenylene ether may be a mixture of two or more kinds of polyphenylene ethers having different reduced viscosities.
[0028] In order to stabilize the (B) polyphenylene ether, various known stabilizers may be blended into the resin composition. Examples of the stabilizer include metal stabilizers such as zinc oxide and zinc sulfide, and organic stabilizers such as hindered phenol stabilizers, phosphorus stabilizers, and hindered amine stabilizers. The content of the stabilizer is preferably less than 5 parts by mass based on 100 parts by mass of the polyphenylene ether (B).
[0029] [Content of component (B)] In the resin composition of the present embodiment, the content of the polyphenylene ether (B) is preferably 2.5 to 20 parts by mass, more preferably 5 to 15 parts by mass, and even more preferably 10 to 15 parts by mass, relative to 100 parts by mass of the total of components (A), (B), and (C).
[0030] [(C) Styrene-based resin] In the present embodiment, the styrene resin (C) may be, but is not limited to, a homopolymer of a styrene compound, a copolymer of two or more styrene compounds, or a polymer obtained by polymerizing a styrene compound and a compound copolymerizable with the styrene compound in the presence of a rubber polymer. Examples of the styrene compound include styrene, α-methylstyrene, 2,4-dimethylstyrene, monochlorostyrene, p-methylstyrene, p-tert-butylstyrene, and α-ethylstyrene. Component (C) is preferably a homopolymer of styrene.
[0031] [Content of component (C)] In the resin composition of the present embodiment, the content of the (C) styrene-based resin is preferably 5 to 22.5 parts by mass, more preferably 10 to 20 parts by mass, and even more preferably 10 to 15 parts by mass, relative to 100 parts by mass of the total of components (A), (B), and (C).
[0032] [(D) Compatibilizer] From the viewpoint of improving the compatibility of the polyamide and the polyphenylene ether, the resin composition in the present embodiment preferably further contains a compatibilizer (D). The main purpose of using the compatibilizer (D) is to improve the physical properties of the mixture of the polyamide and the polyphenylene ether.
[0033] (D) Compatibilizer means a polyfunctional compound that interacts with polyphenylene ether, polyamide, or both. Such interaction may be chemical (e.g., grafting) or physical (e.g., changing the surface properties of the dispersed phase). In either case, the compatibility of the resulting mixture of polyamide and polyphenylene ether is improved.
[0034] Examples of the (D) compatibilizer include those described in JP-A-8-48869 and JP-A-9-124926. All of these known compatibilizers can be used, and two or more of them can also be used in combination. Among the various (D) compatibilizers described above, one or more selected from the group consisting of citric acid, maleic acid, itaconic acid, and anhydrides thereof are preferred, with maleic anhydride and / or citric acid being more preferred.
[0035] The content of the (D) compatibilizer is preferably 0.01 to 10 parts by mass, more preferably 0.10 to 5 parts by mass, and even more preferably 0.10 to 2 parts by mass, relative to 100 parts by mass of the total of components (A), (B), and (C).
[0036] [(E) Inorganic filler] The inorganic filler (E) of this embodiment is not limited to the following, but may be, for example, fibrous inorganic fillers such as glass fiber, potassium titanate fiber, gypsum fiber, brass fiber, stainless steel fiber, steel fiber, ceramic fiber, and boron whisker fiber; plate-like inorganic fillers such as mica, talc, kaolin, calcined kaolin, and glass flakes; granular inorganic fillers such as titanium oxide, apatite, glass beads, silica, calcium carbonate, and carbon black; and needle-like inorganic fillers such as wollastonite and xonotlite. Among these, preferred are fibrous inorganic fillers, plate-like inorganic fillers, and needle-like inorganic fillers, more preferably talc, wollastonite, glass flakes, and glass fiber, even more preferably glass flakes and glass fiber, and even more preferably glass fiber. These inorganic fillers may be used alone or in combination of two or more. The inorganic filler may be surface-treated by a known method using a surface treatment agent such as a silane coupling agent.
[0037] The content of the (E) inorganic filler is preferably 30 to 60 mass %, more preferably 30 to 50 mass %, and even more preferably 40 to 50 mass %, when the entire resin composition is taken as 100 mass %.
[0038] [(F) Carbon Black] The carbon black (F) in this embodiment is blended as a component for imparting black color and improving weather resistance.
[0039] The average primary particle size of (F) carbon black is 20 nm or less, preferably 5 to 20 nm, and more preferably 10 to 20 nm. From the viewpoint of weather resistance, it is preferably 20 nm or less, and from the viewpoints of dispersibility in the resin composition and color unevenness of the molded product, it is preferably 5 nm or more. The average primary particle size can be measured using an electron microscope, specifically, by the method described in the Examples.
[0040] The carbon black (F) may be used alone or in combination of two or more kinds having different average primary particle sizes. Also, a master batch made by pre-kneading with polystyrene may be used.
[0041] In the resin composition of the present embodiment, the content of (F) carbon black is 2 to 7 parts by mass, preferably 2 to 6 parts by mass, more preferably 2 to 5 parts by mass, even more preferably 2 to 4 parts by mass, and even more preferably 2 to 3 parts by mass, based on 100 parts by mass of the total of components (A), (B), and (C). From the viewpoint of weather resistance, it is preferably 2 parts by mass or more, and from the viewpoint of mechanical properties, it is preferably 7 parts by mass or less.
[0042] In the resin composition of the present embodiment, the mass ratio (C) / (B) of component (B) to component (C) is preferably 1-3, more preferably 1-2.5, and even more preferably 1-2. By setting the ratio (C) / (B) within the above range, photodegradation and a decrease in the glass transition temperature of the particles composed of (B) and (C) dispersed in component (A) are suppressed, and a good balance between weather resistance and mechanical properties can be obtained.
[0043] [Other additives] Examples of other additive components include other thermoplastic resins such as polyesters and polyolefins, plasticizers (low molecular weight polyolefins, polyethylene glycol, fatty acid esters, etc.), antistatic agents, nucleating agents, flow improvers, anti-dripping agents, reinforcing agents, various peroxides, spreading agents, organic heat stabilizers such as copper-based heat stabilizers and hindered phenol-based oxidative degradation inhibitors, antioxidants, ultraviolet absorbers, light stabilizers, etc.
[0044] A specific preferred amount of each of the other additive components is 15% by mass or less, more preferably 13% by mass or less, and even more preferably 10% by mass or less, when the entire resin composition is taken as 100% by mass. Furthermore, the total amount of other additive components is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, when the entire resin composition is taken as 100% by mass.
[0045] Furthermore, relative to 100 parts by mass of all thermoplastic resin components, the total content of components (A), (B), and (C) is preferably 70 parts by mass or more, more preferably 80 parts by mass or more, even more preferably 90 parts by mass or more, and even more preferably 95 parts by mass or more, and may be 100 parts by mass.
[0046] [Method for producing resin composition] The resin composition of the present embodiment can be produced by a conventionally known melt-kneading method using the above-mentioned components (A) to (F) and, if necessary, additives. Examples of the method include melt kneading using a single screw extruder, a twin screw extruder, a roll, a kneader, a Brabender plastograph, a Banbury mixer, etc., among which a method using a twin screw extruder is preferred, and in particular, a method using a twin screw extruder equipped with an upstream supply port and one or more downstream supply ports is even more preferred. The melt-kneading temperature is preferably within the range of 280 to 360°C.
[0047] [Molded products and their manufacturing methods, etc.] A molded article can be produced by molding the resin composition of the present embodiment using a conventionally known molding method such as injection molding, extrusion molding, press molding, blow molding, calendar molding, and casting molding. That is, the molded article of the present embodiment contains the resin composition. The molding method is not particularly limited, and a known method can be used. For example, a molded product having a predetermined shape can be produced by melting a resin composition in a cylinder of an injection molding machine and injecting the melt into a mold having a predetermined shape. In addition, a fibrous molded product can be produced by melting the resin composition in an extruder with a controlled cylinder temperature and spinning it through a die nozzle. Furthermore, a film- or sheet-shaped molded product can be produced by melting the resin composition in an extruder with a controlled cylinder temperature and extruding it from a T-die. Furthermore, the molded article produced by such a method may have a coating layer formed on the surface thereof, which may be made of paint, metal, or other types of polymers. That is, a laminate may be formed which includes the molded article of the present embodiment and a coating layer formed on at least a part of the surface of the molded article. The coating layer may be one layer or two or more layers. The lamination method is not particularly limited, and a suitable method may be adopted depending on the intended use and the shape of the molded article. EXAMPLES
[0048] Hereinafter, the present embodiment will be described with reference to specific examples and comparative examples, but the present embodiment is not limited thereto. The raw materials and measurement methods used in the examples and comparative examples are shown below.
[0049] 〔raw materials〕 ((A) Polyamide) <(A) Polyamide 9,T (hereinafter referred to as "PA9T")> PA9T was used, which had a MFR of 70 g / 10 min measured at 300° C. and 1 kg according to ISO 133. The PA9T had dicarboxylic acid units containing 100 mol % terephthalic acid units and diamine units containing 100 mol % 1,9-nonanediamine units and / or 2-methyl-1,8-octanediamine units.
[0050] <(B) Polyphenylene ether (hereinafter referred to as "PPE")> The PPE used had a reduced viscosity of 0.40 dL / g measured at 30° C. using an Ubbelohde viscometer at a concentration of 0.5 g / dL in chloroform solvent.
[0051] <(C) Styrene-based resin (hereinafter referred to as "PS")> General purpose polystyrene (product name: STYRON 660 (registered trademark), manufactured by The Dow Chemical Company) was used.
[0052] <(D) Compatibilizer> Maleic anhydride (special grade reagent) (manufactured by Wako Pure Chemical Industries, Ltd.) was used.
[0053] ((E) Inorganic filler) <(E-1) Glass fiber> Glass fiber ("ECS03-T747" manufactured by Nippon Electric Glass Co., Ltd., fiber diameter 13 μm, chop length 3 mm) was used. <(E-2) Glass flakes> Glass flakes ("MEG160FYX (6145)" manufactured by Nippon Sheet Glass Co., Ltd.) were used.
[0054] ((F) Carbon Black) <(F-1) Carbon black-containing masterbatch> General purpose polystyrene-based masterbatch pellets (F-1) containing 50% by mass of carbon black with a primary particle diameter of 16 nm were used. Of the masterbatch pellets used, 50% by mass was calculated as (F) carbon black, and the remaining 50% by mass of polystyrene was calculated as (C) styrene-based resin.
[0055] <(F-2) Carbon black-containing masterbatch> General purpose polystyrene-based masterbatch pellets (F-2) containing 50% by mass of carbon black with a primary particle diameter of 40 nm were used. Of the masterbatch pellets used, 50% by mass was calculated as (F) carbon black, and the remaining 50% by mass of polystyrene was calculated as (C) styrene-based resin.
[0056] The average primary particle size was measured by arithmetic average of 10 randomly selected particles using an electron microscope.
[0057] [Method of measuring characteristics] (1) Melt Volume Flow Rate (MVR) The pellets of the obtained resin composition were subjected to MVR (cm) at 320°C under a load of 5 kg in accordance with ISO1133. 3 / 10min) was evaluated. The larger the value, the better the fluidity was judged to be.
[0058] (2) Deflection temperature under load (DTUL) The obtained pellets of the resin composition were fed to a small injection molding machine (product name: IS-100GN, manufactured by Toshiba Machine Co., Ltd.) with a cylinder temperature set to 320°C, and an ISO dumbbell for evaluation was produced under the condition of a mold temperature of 110°C. The ISO dumbbell was also cut to produce a test piece for measuring the deflection temperature under load (DTUL). The deflection temperature under load: DTUL (ISO 75: 1.8 MPa load) (°C) was measured using the test piece for measuring the deflection temperature under load. It was determined that the larger the value, the more excellent the heat resistance.
[0059] (3) Tensile strength Using the JIS K7139 ISO dumbbell molded in (2) above, the tensile strength was evaluated by measuring the tensile yield strength (MPa) at a temperature of 23°C and at a speed of 5 mm / min in accordance with ISO 527. It was determined that the higher the value, the better the mechanical strength.
[0060] (4) Notched Charpy impact strength Using the JIS K7139 ISO dumbbell molded in (2) above, a test piece for measuring Charpy impact strength was prepared. Using the above test piece for measuring Charpy impact strength, the Charpy impact strength (kJ / m 2 The larger the value, the better the impact resistance was judged to be.
[0061] (5) Weather resistance The obtained pellets of the resin composition were fed into a small injection molding machine (product name: IS-100GN, manufactured by Toshiba Machine Co., Ltd.) with a cylinder temperature set to 320°C, and molded into a flat plate of 50 mm x 90 mm x 2 mm at a mold temperature of 110°C. The obtained flat plate was placed in a sunshine weather meter, and the weather resistance was evaluated under conditions of a wavelength of 340 nm, an illuminance of 0.35 W, and no rain spray. The surface of the flat plate was observed after 2000 hours, and those that showed no change in color or surface roughness were marked with an ◎, those that showed a change only in surface roughness were marked with a ○, those that showed a change in color were marked with a △, and those that showed changes in both color and surface roughness were marked with an ×.
[0062] [Examples 1 to 5 and Comparative Examples 1 to 5] A twin-screw extruder [ZSK-26MC, Coperion (Germany)] was used, which has three supply ports on the upstream, center, and downstream sides in the direction of the raw material flow. The positions of the supply ports are as follows: when the total length of the extruder cylinder is 1.0, the supply port at L=0 from the upstream is the upstream supply port, the supply port at L=0.4 is the center supply port, and the supply port at L=0.6 is the downstream supply port. The raw material was supplied to the upstream supply port, the center supply port, and the downstream supply port using a hopper. The temperature from the upstream supply port to the center supply port was set at 320°C, and the temperature downstream of the center supply port was set at 310°C. The screw rotation speed was 300 rpm, and the discharge rate was 15 kg / h. In addition, openings were provided in the block immediately before the cylinder block with the central supply port and in the cylinder block immediately before the die, and the remaining volatile matter and oligomers were removed by vacuum suction. The degree of vacuum (absolute pressure) at this time was 60 Torr. According to the composition shown in Table 1 below, the respective raw materials were supplied and melt-kneaded. The strand extruded from the tip of the extruder die was cooled in a SUS strand bath filled with cooling water, and then cut with a strand cutter to obtain resin composition pellets. In order to adjust the moisture content of the obtained resin composition pellets, after extrusion, the pellets were dried for 1 hour in a dehumidifying dryer set at 120° C., and then placed in an aluminum-coated moisture-proof bag. The moisture content of the resin composition pellets at this time was approximately 200 to 300 ppm. The resin composition pellets thus obtained were used to carry out the above-mentioned evaluations, and the results are shown in Table 1 below.
[0063] [Table 1] [Industrial Applicability]
[0064] INDUSTRIAL APPLICABILITY The resin composition of the present invention has an excellent balance of mechanical properties and weather resistance, and therefore can be suitably used particularly for various electric and electronic parts, various battery parts, various optical parts, and the like.
Claims
1. (A) Polyamide (B) Polyphenylene ether (C) Styrene-based resin (D) Compatibilizer (E) Inorganic filler (F) Carbon black A resin composition comprising: the component (A) is a polyamide having dicarboxylic acid units (a) containing 60 to 100 mol % of terephthalic acid units and diamine units (b) containing 60 to 100 mol % of aliphatic diamine units having 9 to 12 carbon atoms; the mass ratio (C) / (B) of the component (B) to the component (C) is 1 to 3; The component (D) is a polyphenylene ether, a polyamide, or a polyfunctional compound that interacts with both of them, The resin composition, characterized in that the average primary particle diameter of the component (F) is 20 nm or less, and the content of the component (F) is 2 to 7 parts by mass per 100 parts by mass of the total of the components (A), (B), and (C).
2. The resin composition described in claim 1, characterized in that the (D) compatibilizer is one or more selected from the group consisting of citric acid, maleic acid, itaconic acid, and anhydrides thereof.
3. The resin composition according to claim 1 or 2, wherein the component (A) is 60 to 90 parts by mass per 100 parts by mass of the total of the components (A), (B), and (C).
4. The resin composition according to any one of claims 1 to 3, wherein the component (A) has a dicarboxylic acid unit (a) containing 60 to 100 mol% of a terephthalic acid unit, and a diamine unit (b) containing 60 to 100 mol% of a 1,9-nonanediamine unit and / or a 2-methyl-1,8-octanediamine unit.
5. The resin composition according to any one of claims 1 to 4, wherein the component (E) comprises a fibrous inorganic filler or a needle-like inorganic filler.
6. The resin composition according to claim 5 , wherein the fibrous inorganic filler is a glass fiber.
7. The resin composition according to any one of claims 1 to 4, wherein the component (E) comprises a plate-like inorganic filler.
8. The resin composition according to claim 7 , wherein the plate-like inorganic filler is glass flakes.
9. A molded article comprising the resin composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Polyamide resin composition
JP1996134347A
Polyamide resin composition and molding consisting of the same
JP2006137815A
Polyamide / polyphenylene ether resin composition
JP2007154127A
Heat-resistant resin composition
JP2007182550A
Polyamide-polyphenylene ether-based resin film
JP2007217620A